Déjàvu Project as a digital solution to help the appraisal of documents focused on digital humanities - Hernandez, Bianca; Vital, Luciane Paula (Advanced Notes in Information Science, 2023)
This article aims to analyze the DéjàVu Project as a complementary solution to the archival function of document appraisal in the digital humanities. It is exploratory and qualitative research with technical procedures related to the bibliographic study of digital humanities and documents. The digital solution refers to the combination of digital activities of data collection and cleaning, followed by organization and synchronization for later understanding and inference in various fields, including appraisal support. We concluded that using the solution developed in the DéjàVu Project has the potential to be used complementary to document appraisal. It provides a context substrate for a more accurate, pluralistic, and representative appraisal of social demands. It primarily facilitates the attribution of social values in the Macro-Appraisal process.